“A semana inteira na lavoura, aos domingos ao cinema pela noite”: cotidiano e cultura (Cachoeirinha-PR, 1930-1945) - Matos Neto, Osvaldo Carneiro de (2020)
This written work seeks to contribute to studies on daily life and culture by the various subjects who experienced the transformations that took place in Cachoeirinha and in the other districts and adjacent rural blocks, in the municipality of Jaguariaíva, Paraná, between 1930 and 1945. The analysis of the conjuncture that led to these transformations starts from a broad researched documentation, such as reports from the government and its secretariats, laws and periodicals, in which the actions of foreign companies that have settled in the state are noticeable, as well as those companies‟ relations with the executive and legislative authorities. In this regard, it is observed how the construction of the São Paulo - Rio Grande Railroad by Brazil Railway, Southern Brazil Lumber's logging and land exploration, and the paper production initiated by The Oversea Company impacted the way of life of the local population. For such investigation, criminal cases related to various crimes were also used. Those cases allowed the access to experiences of farmers, workers, women and children, in various spheres of their lives, such as at work, affectivities, festivities, beliefs and religiosities. Thus, gender relations, popular cultures and state regulatory actions through the judicial and police apparatus were questioned. The tension and resistances resulting from the process were highlighted starting from the practical interventions, carried out by the people, in the moments of leisure and relaxation, such as the horse races and the cinema or even of the festivities and sounds expressed in the rural balls and in the Jazz bands. Correlations that show clashes and hybridity between what was supposedly considered "archaic" and "modern", raising questions about the notions of "culture" and "tradition", highlighting the existence of varied rhythm and multiple temporalities in daily life. In this debate, interventionist policies of cultural diffusion, common to the Vargas governments and to the “golden age” of radio, as well as modernist reflections on a conciliatory notion of “Brazilianness” are also considered